2018
DOI: 10.1158/1541-7786.mcr-18-0087
|View full text |Cite
|
Sign up to set email alerts
|

Novel lncRNA LINC00844 Regulates Prostate Cancer Cell Migration and Invasion through AR Signaling

Abstract: : The human genome is mostly transcribed, yielding a rich repository of noncoding transcripts that are involved in a myriad of biological processes including cancer. However, how many noncoding transcripts such as long noncoding RNAs (lncRNA) function in cancer is still unclear. This study identified a novel set of clinically relevant androgen-regulated lncRNAs in prostate cancer. Among this group, was demonstrated to be a direct androgen-regulated target that is actively transcribed in androgen receptor (AR)-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 50 publications
5
58
0
Order By: Relevance
“…Previous studies have reported that non‐coding RNAs (ncRNAs) play important roles in cancer development, tumor formation, immune response, and inflammation of many cancers, which includes small ncRNAs (<200 nucleotides at length) and long ncRNAs (lncRNA, >200 nucleotides at length) (Bushati and Cohen, ; Krol et al, ; Perkel, ; Rapicavoli et al, ; Tao et al, ). Emerging evidence suggested that lncRNA is involved in cell proliferation, invasion, migration, and apoptosis in multiple types of cancers, including PCa (Guo et al, ; Li et al, ; Zhang et al, ; Lingadahalli et al, ). Chakravarty et al () reported that lncRNA NEAT1 was a critical modulator in cell progression of PCa.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that non‐coding RNAs (ncRNAs) play important roles in cancer development, tumor formation, immune response, and inflammation of many cancers, which includes small ncRNAs (<200 nucleotides at length) and long ncRNAs (lncRNA, >200 nucleotides at length) (Bushati and Cohen, ; Krol et al, ; Perkel, ; Rapicavoli et al, ; Tao et al, ). Emerging evidence suggested that lncRNA is involved in cell proliferation, invasion, migration, and apoptosis in multiple types of cancers, including PCa (Guo et al, ; Li et al, ; Zhang et al, ; Lingadahalli et al, ). Chakravarty et al () reported that lncRNA NEAT1 was a critical modulator in cell progression of PCa.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide sequencing has revealed the involvement of more and more lncRNAs in different types of cancers [10] . Lingadahalli et al [19] performed in vivo and in vitro experiments to confirm the participation of LINC00844 in tumour metastasis partly through its effect on the expression of NDRG1 in prostate cancer. High expression of lncPARP1 may serve as an adverse prognosis factor for HCC [20] .…”
Section: Discussionmentioning
confidence: 99%
“…A study reported that NDRG1 overexpression may inhibit the expression of E-cadherin and enhance the expression of Snail, and consequently regulate tumour growth and metastasis in oesophageal squamous cell carcinoma [18] . Another study reported that LINC00844 exerted its antitumour activity by regulating the expression of NDRG1 in prostate cancer [19] . However, the biological function and underlying molecular mechanisms of LINC00844 in HCC are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs could regulate PC development through different signaling pathways . Previous studies have indicated the association between PC and Notch‐1 signaling pathway .…”
Section: Discussionmentioning
confidence: 99%